Effect of vegetable and mineral oil-in-water emulsion cutting fluids in turning AISI 4340 steel with coated carbide tools / Sunday Albert Lawal - Sunday, Albert Lawal (2013)
Cutting fluids have been used extensively and play a significant role in machining processes. Cutting fluids affect the productivity of machining operations, tool life, quality of workpiece and prevent the cutting tool and machine from overheating as well. In general, a successful cutting fluid must not only improve the machining process performance, but also fulfill a number of requirements which are non-toxic, non-harmful to health for operators, not a fire hazard, not smoke or fog in use and cost less. One of the drawbacks of using conventional (mineral) oil based cutting fluids is the waste disposal after being used. Mineral oil has also poor biodegradability thus induces the potential for long term pollution of the environment. In this study, a comprehensive literature review of application of vegetable oil-based cutting fluids in machining different workpiece materials with different tool materials was done. This study is divided into two main sections, the first section focused on the properties of palm kernel and cottonseed oils and formulation of oil-in-water emulsion cutting fluids using the two oils. The selection of cutting fluid additives (emulsifier, anticorrosive agent, antioxidant and biocide) for the formulation of oil-in-water emulsion using palm kernel and cottonseed oils are not dangerous or problematic to the environment or harmful to workers. The formulation of cutting fluid was based on Design of Experiment (DOE) of 24 full factorial designs and statistical analysis of the response value (pH) was employed using version 6 of DOE® software. The pH values of 10.46 and 10.98 were obtained for the palm kernel oil and cottonseed oil respectively, which are within the acceptable standard for cutting fluid for machining processes. The second section considered the effect of the two formulated oil-in-water emulsion cutting fluids in turning AISI 4340 steel with coated carbide tools and compared with conventional (mineral) oil-based cutting fluid. Taguchi method with L27 (34) orthogonal array for experimentation was adopted. Cutting speed, feed rate and depth of cut were output variables considered for experimentation. In addition to the cutting parameters, type of cutting fluid used was also considered as one of the critical input parameters while designing the experiment. Cutting force, surface roughness and tool wear are the output parameters obtained from the trials conducted as per L27 array experimentation and further analyzed. Minitab 14 statistical analysis software widely used in engineering application was used in the analysis of signal- to- noise (S/N) (dB) ratio and ANOVA for surface roughness, cutting force and tool wear. The ANOVA analysis shows that cutting speed (64.46%) and feed rate (32.19%) significantly affected surface roughness. Depth of cut (33.15%) and cutting fluid (51.12%) significantly affected cutting force and while cutting speed (85.36%) and feed rate (4.81%) significantly affected tool wear. The effect of cutting fluids on the type of chip formed was equally accounted for. Confirmation tests applied for Taguchi results and regression equations indicate reliable results.